Analisis Prediksi Kondisi Financial Distress Debitur Pasca Erupsi Gunung Sinabung - Munawarah Munawarah; Wenny Anggeresia Ginting (Universitas Negeri Medan, 2019)
One of the factors causes financial distress is a natural disaster such as Eruption of Sinabung in Karo. By using the financial’s debtor performance (financial ratios), Bank officer has an analyzing system to detect the ability of the debtor to pay their liabilities. The aim of this research is to design prediction model and analyze whether Working Capital to Total Asset, Sales to total Asset, Total Debt to Total Asset, Total Debt to Total Equity, and Earning Before Interest and Taxes to Total Asset have significant influence to predict the financial distress or non financial distress of debtor while the Sinabung eruption is happening. The analysis method using Binary logistic with dummy data on the dependent variable. The result shows that only Total Debt to Total Asset has positive and significant effect to predict the probability of debitor’s financial distress. The possibility of predictions accurate is about 86,7%. The value Nagelkerke R Square is 67,8 % which indicates that the variation of financial distress and non financial distress’s probability can be explained by variation of Working Capital to Total Asset, Sales to total Asset, Total Debt to Total Asset, Total Debt to Total Equity, and Earning Before Interest and Taxes to Total Asset. While 32,2 % can be explained by others factor exclude of the research.